The Role of Productive Waqf in Developing the Economy and Social Perspective of Behavioral Finance Theory - Nurus Sa’adah (Al-Fadilah: Islamic Economics Journal, 2026)
This study examines the role of productive waqf in economic and social development from a behavioral finance theory perspective. The author explains the importance of waqf in empowering low-income communities, particularly those in low-income communities. Waqf funds can be allocated to support and empower economic and social aspects by providing business capital and providing training and mentoring to improve the skills and capacity of micro-communities. The research method used is a literature review, focused on the analysis and synthesis of relevant papers and data. The results indicate that productive waqf has a positive impact on social welfare and economic growth in Indonesia, including socio-religious life, equitable development, poverty alleviation, reduced unemployment, expanded employment opportunities, and economic growth. If optimally managed, waqf will have a positive impact, significantly boosting sustainable economic growth and creating an independent and productive society. Therefore, it is important to emphasize the government's need to provide greater support to utilize the potential of waqf instruments in Indonesia. From a behavioral finance perspective, this relates to financial management because it is a way to obtain and use money appropriately, thus implementing hablum minallah and hablum minnannas.